Field report PAC 671: WT NG & Co / Nur Afiqah Mohamad Zulkifli - Mohamad Zulkifli, Nur Afiqah (Universiti Teknologi MARA, Terengganu, 2024)
I am currently enrolled in an internship program at WT NG & Co, which is based in Kuantan, Pahang from March 4 to August 23, 2024. This company has two branches in the states of Kuantan, Pahang, and Kuala Lumpur. WT NG & Co. offers expert audit, taxation, advisory, and accounting consulting services to a wide range of clients in Malaysia. This company has three departments in its Kuantan branch which are the tax and accounting departments on the ground floor and the audit and secretary departments located on the second floor. I was assigned to the accounting and taxation department throughout my whole internship period. I had the privilege of working in an environment that encourages a dedication to providing excellent service. I was exposed to a wide range of industries and job scopes due to the different business nature of the different clients. WT NG & Co has provided a conducive and comfortable environment where I can work more effectively and efficiently. Moreover, I get to expand my exposure by learning about various businesses and build career sustainability through a diverse set of experiences.